Pregnant Women’s Satisfaction with the Antenatal Services Provided by Midwives in Government-Owned Health Care Facilities in South-South, Nigeria - Nwamaka, Kanikwu Phoebe; Nkechi , Chiejina Edith (International Journal For Research In Health Sciences And Nursing, 2020)
Background: The satisfaction of pregnant women with the quality of antenatal services results in adherence to antenatal care regimen, return for subsequent visits and better materno-fetal outcomes. Objectives: The objectives of the study were to determine pregnant women’s satisfaction with the antenatal services they receive from midwives with regard to general satisfaction, satisfaction with technical quality of the antenatal care provided by midwives, satisfaction with interpersonal aspect of the services, communication, financial, time spent with the midwives and availability/access/convenience of the antenatal services provided by the midwives in the health care facilities in South-South Nigeria. Materials and Methods: The study was a cross sectional survey research design. A total of 1500 pregnant women were selected for the study using multi-stage sampling technique. Patient Satisfaction Questionnaire was the instrument used for data collection. The reliability of the instrument was established through test-retest method using Cronbach’s Alpha which yielded a co-efficient of 0.709. Data collected were analyzed using frequencies, percentages, mean and standard deviation to determine the objectives of the study. Factorial Analysis of Variance was used to test the hypothesis at 0.05 level of significance. Results: The result showed mean of 56.12 10.17 for general satisfaction, satisfaction with technical quality mean = 65.04 7.12, interpersonal satisfaction mean = 71.07 11.23, satisfaction with communication mean 63.07 16.59, satisfaction with financial aspect mean = 59.75 9.88, mean for time spent with midwife = 73.33 29.82, and satisfaction with convenience of antenatal services had mean of 59.86 7.62. There were significant associations between the satisfaction expressed by pregnant women and their occupation F=3.088, p-value = 0.027, and religion F=5.469, p-value=0.016. Conclusion: Pregnant women were satisfied with the antenatal services provided by midwives in Government-owned Health care facilities in South-South Nigeria. Non-governmental organizations should support the funding of human and material resources needed to further improve the performance of midwives and maintain satisfaction of pregnant women with antenatal services.